The impact of automation system on the job satisfaction and performance level of the UPV Miag-ao and Iloilo City cash section employees - Franco, Arlene; Hormillosa, Celeste Joy.; Justiniani, Jo Elizabeth; Panganiban, Rosario; Provido, Lores Leticia (1999)
This research sought to dtermine the impact of automation system on the level of job satisfaction and performance. Seven employees of cash office in both Iloilo and Miag-ao campuses were the respondnets of this study. Standard scale developed by Paul E. Spector of the Department of Psychology of the University of south Florida was used to measure job satisfaction. Secondary data obtained from the Human Resources Development Office (HRDO) was used to determine performance level of the employees before and after the implementation od the automation system. The result of Pearson-product moment correlation revealed that performance and job satisfaction has insignificant positive relationship ( r = .214, p. .05). Through t-test the researchers found out that performance level increased during automation compared to performance prior to the introduction of automation system ( t₍₇ٖٖ₁₎=8.25.t=1.89).
Research Paper (Mgt 200 - Business Research) -- Iloilo City : UPV-CM, March 19, 1999.